Approaches to improving patient safety in integrated care: a scoping review. Issue 4 (4th April 2023) - Lalani, Mirza; Wytrykowski, Sarah; Hogan, Helen
Abstract : Objectives: This scoping review aimed to establish the approaches employed to improving patient safety in integrated care for community-dwelling adults with long-term conditions. Design: Scoping review. Setting: All care settings. Search strategy: Systematic searches of seven academic and grey literature databases for studies published between 2000 and 2021. At the full-text review stage both the first and second reviewer (SW) independently assessed full texts against the eligibility criteria and any discrepancies were discussed. Results: Overall, 24 studies were included in the review. Two key priorities for safety across care boundaries for adults with long-term conditions were falls and medication safety. Approaches for these priorities were implemented at different levels of an integrated care system. At the micro-level, approaches involved care primarily in the home setting provided by multi-disciplinary teams. At the meso-level, the focus was on planning and designing approaches at the managerial/organisational level to deliver multi-disciplinary care. At the macro-level, system-wide approaches included integrated care records, training and education and the development of care pathways involving multiple organisations. Across the included studies, evaluation of these approaches was undertaken using a wide range of process and outcome measures to capture patient harm and contributory factors associated with falls and medication safety. Conclusions: For integrated care initiatives to fulfil their promise of improving care for adults with long-term conditions, approaches to improve patient safety need to be instituted across the system, at all levels to support the structural and relational aspects of integrated care as well as specific risk-related safety improvements.